(untitled) (Bangladesh Journal of Medical Science, 2024)
Objective:Application of Laryngeal Mask Airway (LMA) as a ventilation method has been rarely explored in short and medium period orthopedic operations. In this study, we evaluated ventilatory efficacy of LMA in patients admitted to Ho Chi Minh City Orthopedic and Rehabilitation Hospital, Vietnam via a number of patient indicators including changes of pulse, blood pressure, airway pressure, SpO2 and pressure of CO2 at the end of an exhaled breath (EtCO2). Method: A total of 154 emergency and elective surgery cases with anesthesia were selected for the study. Result: One minute after LMA insertion to discontinuation of anesthetic, we recorded slower pulse of patients but only twenty-six cases (16.9%) required intravenous administration of atropine. Blood pressure of patients dropped after 1 minute following LMA insertion but then recovered afterward and only nine cases (5.8%) needed administration of ephedrine. Conclusion: After surgery, only eleven (7.15%) patients experienced oral mucosal bleeding but no further special treatment was used. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 207-213